EXPERIMENTAL TOXIC HEPATITIS LEADS TO PROGRESSIVE RETINAL NEUROVASCULAR DEGENERATION - Gulnoza O. Khidirova; Abboskhon B. Burkhonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Toxic hepatitis is accompanied by pronounced systemic metabolic disturbances that extend beyond hepatic tissue and involve extrahepatic organs, including the retina. The present study was designed to characterize morphological alterations of the retinal layers in an experimental model of toxic hepatitis and to evaluate the potential protective effects of hepatoprotective therapy. Thirty adult rats were randomly allocated into three groups: intact control, toxic hepatitis, and toxic hepatitis treated with silymarin. Retinal specimens were subjected to histological and histochemical examination using hematoxylin–eosin, periodic acid–Schiff (PAS), Nissl staining, and silver impregnation techniques. Induction of experimental toxic hepatitis led to marked disorganization of retinal laminar architecture, thickening of retinal vascular walls, degeneration of photoreceptor elements, and a significant decrease in ganglion cell density (p < 0.05). PAS staining demonstrated enhanced accumulation of glycoprotein components within the walls of retinal microvessels, indicating metabolic and structural vascular impairment. Administration of silymarin resulted in partial attenuation of both vascular and neuronal damage; however, complete restoration of normal retinal morphology was not achieved. Overall, the obtained results indicate that retinal structural alterations mirror systemic toxic injury associated with experimental toxic hepatitis, supporting the retina as a sensitive morphological indicator of extrahepatic manifestations of hepatic pathology.